2015
DOI: 10.1590/0037-8682-0107-2015
|View full text |Cite
|
Sign up to set email alerts
|

Performance of direct immunofluorescence assay for the detection of human metapneumovirus under clinical laboratory settings

Abstract: DIF is not very sensitive under clinical laboratory settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…Similar results were reported by different investigators: 94.1% in Italy (41), 97% in Japan (8), 100% in Canada (42) and 99% in Brazil (43). In contrast, the analytical sensitivity (50%) was found to be lower than studies (44) reported 100% sensitivity and 89% specificity of DFA when compared to RT-PCR assay and concluded that DFA can be securely used in hMPV screening tests.…”
Section: Discussionsupporting
confidence: 83%
“…Similar results were reported by different investigators: 94.1% in Italy (41), 97% in Japan (8), 100% in Canada (42) and 99% in Brazil (43). In contrast, the analytical sensitivity (50%) was found to be lower than studies (44) reported 100% sensitivity and 89% specificity of DFA when compared to RT-PCR assay and concluded that DFA can be securely used in hMPV screening tests.…”
Section: Discussionsupporting
confidence: 83%
“…In 2010, hMPV infections occurred throughout three seasons (autumn, winter, and spring), whereas hRSV presented the same incidence peak as observed in the other years. hMPV infections occur throughout the year; however, more cases have been detected in winter and spring in other studies 15,40,41 . Therefore, the seasonal occurrence of hMPV appears to coincide with hRSV infections 37,39,42,43 .…”
Section: Discussionmentioning
confidence: 73%
“…Rio Grande do Sul is a state located in South Brazil and divided into several geographic regions with subtropical and humid climate. Respiratory infections are important public health problems in this state, since it presents one of the coldest climates of the country 14,15,35 . The present study demonstrated that hMPV circulated mainly in EWs in the winter and in the beginning of spring in 2009, 2010, and 2011.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations